Perbandingan Metode Simple Additive Weighting (SAW) dan ELECTRE Dalam Pemilihan Tempat Kos di Area Kampus Purwokerto - Corie Mei Hellyana; Warjiyono Warjiyono (Universitas Bina Sarana Informatika, 2018)
Abstract - Boarding house is the second place to live after living with parents. Boarding houses are usually chosen by someone who lives far from parents with the interests of studying or working. But in general boarding houses are identical to someone who is in school or college. With the many universities or educational institutions in the city of Purwokerto, many people rent their houses as boarding houses. But sometimes many boarding house residents move around for various reasons, such as rising boarding prices, far from the place of study, far from public facilities and so on. Therefore, it is necessary to choose a boarding house to reduce boarding house occupants who move. In choosing this boarding house, ELECTRE and SAW methods are used as tools to get a picture of the best boarding houses. With this method the weighting is done to get the percentage of matches for the recommended boarding house according to the criteria. Keywords: boarding, Electre, SAW, criteria